2019
DOI: 10.3390/genes10121032
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Technologies and Strategies for the Management of Retinoblastoma

Abstract: Retinoblastoma (RB) is an inherited retinal disorder (IRD) caused by the mutation in the RB1 gene or, rarely, by alterations in the MYCN gene. In recent years, new treatment advances have increased ocular and visual preservation in the developed world. The management of RB has improved significantly in recent decades, from the use of external beam radiation to recently, more localized treatments. Determining the underlying genetic cause of RB is critical for timely management decisions. The advent of next-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…However, the aforementioned methods lack specificity, and exhibit destructive injuries, low safety, serious systemic and/or local adverse effects and other problems, such as tumor implantation and induction of secondary malignant tumors (2). With the development of tumor molecular biology and genetic engineering technology, coupled with the anatomical advantages of eyeballs as target tissues in the field of RB therapy, gene therapy, as a new type of biological therapy, has demonstrated good application prospects (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, the aforementioned methods lack specificity, and exhibit destructive injuries, low safety, serious systemic and/or local adverse effects and other problems, such as tumor implantation and induction of secondary malignant tumors (2). With the development of tumor molecular biology and genetic engineering technology, coupled with the anatomical advantages of eyeballs as target tissues in the field of RB therapy, gene therapy, as a new type of biological therapy, has demonstrated good application prospects (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, in developing countries, the situation is quite critical, probably due to rather high birth rates and limited medical resources. Approximately 40-70% of patients died in some Asian and African countries [4]. The largest hospital in South Western China used to conduct a retrospective study and found the majority of patients presented at advanced stage [5].…”
Section: Backgroundsmentioning
confidence: 99%
“…Retinoblastoma is the most prevalent childhood primary intraocular malignant tumor with incidence of 1 per 15,000–20,000 live births. 1 Although systemic chemotherapy has become the cornerstone in the management of retinoblastoma 2 it is often tough to achieve complete tumor control in the presence of the vitreous seeds. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%